English Teachers’ Experiences with Intervention Strategy Implementation Addressing Literacy Skill Gaps in Progressed Learners - Zulu, Nhlakanipho Brian; Mabalane, Valencia Tshinompheni; Feltman, Moegamat Yusuf (Studies in Learning and Teaching, 2026)
This paper explores Grade 7 English teachers’ experiences in implementing inclusive intervention strategies to address the literacy skills gap for progressed learners. Fewer studies exist for teachers' implementation of intervention strategies for literacy skills gaps and the criteria on which they are based. Thus, the study examines the existing intervention strategies for addressing the literacy skills gap and their effectiveness. A qualitative case study, framed within the interpretivist paradigm, was implemented in six primary schools in the Johannesburg North District. Six Grade 7 English teachers with 4-16 years of experience implementing intervention strategies for progressed learners were purposively selected. Non-participant observation, semi-structured interviews, and document analysis methods were used to collect data, which were then interpreted thematically through the lens of sociocultural learning theory to extract findings, limitations, and recommendations. Findings demonstrated that teachers' intervention strategies are ineffective in marginalized contexts due to the intersectionality of pedagogical and social-related challenges. Additionally, teachers' lack of sufficient training, resources, support, and unclear policy guidelines related to the implementation of support interventions sets them up for failure. Consequently, this study advocates for sufficient teacher training and support focused on their knowledge of intervention strategies for progressed learners and knowledge of teaching literacy.